MULTICULTURAL EDUCATION AND ITS IMPACT ON LANGUAGE DEVELOPMENT: THE CASE OF MILITARY CADETS AT TMA - Demirel, Hakan Hilmi; Akpınar, Kadriye Dilek (International Online Journal of Education and Teaching, 2016)
The purpose of the study was three-fold: First, to determine the perspectives of the international and Turkish military cadets at Turkish Military Academy (TMA) towards multicultural learning environment and cultural diversity. Second, to analyze to what extent the multicultural learning environment affects the language development of both international and Turkish cadets. Third, to identify the observations and suggestions of language instructors about the best practices to be applied in multicultural learning setting. A questionnaire and two proficiency tests were applied on 80 cadets for quantitative data. Qualitative data was gathered from 13 language instructors studying at TMA. It was found that the perspectives of the cadets towards multicultural learning setting were positive. However, the international cadets’ language proficiency developed more than the Turkish cadets. Analysis of the interviews with the language instructors provided important insights into the issue. Key Words : cultural diversity, international student, multicultural learning, TMA.